The Role of ICT in Addressing Corruption Across Political Regimes - Mergen Dyussenov (Department of Government Studies Universitas Muhammadiyah Makassar, 2019)
The paper reviews existing literature on the role of the internet in addressing corruption by breaking it down into instrumental, important, and critical roles, across two types of political regimes – (semi-)authoritarian and democracies. It analyzes the key resources and strategies utilized by governments and activists across these regimes, and looks into the common themes that emerge as a result of analyzing literature sources, i.e. the notion of crisis, lack of a single accepted definition of corruption across nations, factors found to positively correlate with reduced corruption, and the evolving nature of the internet. The paper finds that neither regime can be perfectly immune against mass-scale protests caused by dissatisfaction with worsening corruption. However, the regimes differ in the nature of protests, with semi-authoritarian regimes witnessing more violent and aggressive uprisings fueled by long-accumulated social disappointment with previous repressive regimes than across much of democracies.